Evaluation the efficacy of NB-UVB treatment alone in comparison with combination therapy of NB-UVB and oral prednisolone in treatment of vitiligo - Abdullah Khamees Mohammed Al-Sammarraie, Yasir (Diyala Journal of Medicine, 2024)
Background: The treatment landscape for vitiligo has witnessed diverse approaches yielding variable outcomes. Objective: To discern the optimal approach in terms of both tolerability and efficacy by comparing Narrow Band Ultraviolet B (NB-UVB) phototherapy with adjunctive oral mini pulse (OMP) prednisolone tablets. Patients and Methods: A total of eighty-seven individuals with progressive vitiligo were enrolled in a one-year study, with participants allocated randomly across three study groups through a continuous selection method. Group 1 received a combination of NB-UVB and OMP prednisolone tablets, group 2 underwent NB-UVB treatment only, and group 3 received OMP prednisolone tablets alone. Clinical assessments were conducted at three- and six-month intervals, and statistical analyses were performed utilizing descriptive and bivariate techniques, including the chi-square test, to gauge the significance of differences between the various groups. Results: In Group 1 (NB-UVB + OMP), substantial improvement was observed in 41.4%, accompanied by moderate improvement in 44.8% of patients. Group 2 (NB-UVB) demonstrated marked improvement in 31.0% and moderate improvement in 38.0%. In Group 3 (OMP), a lower proportion experienced marked (13.8%) or moderate (3.4%) improvement. Chi-square test findings indicated that the combination of NB-UVB and OMP correlated significantly with marked and moderate improvement in contrast to OMP alone, with respective values of χ² = 6.434 (p = 0.001) and χ² = 7.831 (p = 0.015) after a six-month follow-up. Conclusion: Through a comprehensive evaluation of three treatment modalities in vitiligo patients, it was established that the sole application of oral mini pulse steroids (OMP) held an adjunctive value, lacking substantial efficacy on its own. Remarkably, the amalgamation of Narrow Band UVB and OMP presented a clear advantage over either treatment administered independently.